dynamics of indicators of agility development at 4-6 year old children under the influence of special exercises aimed at improving the functional state of sensory systems - Moiseienko, Olena; Platova, Anna (Актуальні проблеми фізичного виховання різних верств населення, 2020)
Abstract. Indicators of agility development at 5-6 year old children and their changes after the introduction of exercises into the educational process aimed at improving the functions of sensory systems are given in the article. Keywords: physical qualities, physical education, pre-school children, analyzers. References Vilchkovskyi E. S., Kurok O. I. Theory and methods of physical education of pre-school age children: educational manual for students of pre-school faculties of high. educ. inst. MESU. The 3rd ed., Sumy: University book, 2017. 428 pp. Hlazyrin I. D. The basics of differentiated physical education. Cherkasy, 2003. 352 pp. Kozhukhova N. N., Ryzhkova L. A., Samodurova M. M. Teacher of physical culture in pre-school institutions. Ed. Center «Akademiya». 2002. 320 pp. Masliak I. P., Mameshina M. A. Theory and methods of physical education. Manual remade. Kharkiv: KhSPC, 2018. 180 pp. Moiseienko O. K., Horchaniuk Y. A., Danysh I. V. Dynamics of indicators of the auditory analyzer state at 5-6 year old children under the influence of specially directed exercises. Current problems of physical education of different segments of the population. Kharkiv: KhSPC, 2018. pp. 186–193. Muravyov V. A., Nazarov N. N. Education of physical qualities of pre-school and school age children. Methodical grant, 2004. 112 pp. Sports metrology: theory and practical aspects [Text]: textbook. L. P. Serhiienko; Ministry of Education and Science of Ukraine. 2010. 773 pp. Theory and methods of physical education. Under the red. of T. Y. Krutsevych. Olympic literature, 2017. V. 2. 448 pp. Shesterova L. Ye., Kuzmenko I. A., Maslyak I. P. Motive preparedness of school-age children under the influence of special exercises affecting the state of the acoustic analyzer. Sport science. International scientific journal of kinesiology. 2017. Vol. 10. Issue 2. рр. 97–104.